Predictors of complain behaviour among mobile telecommunication network consumers - Chinedu, Anyanwu Hilary; Haron, Sharifah Azizah; Osman, Syuhaily (Canadian Center of Science and Education, 2017)
This research paper sought to empirically determine the predictors of consumer complain behaviour. High prevalence of anomalies with mobile telecommunication network services without a lasting solution emphasized the significance of the present study. Hawkins, Best, & Coney (2004) consumer complain behavioural framework was used as the study’s theoretical background. It was a quantitative study which employed a cross-sectional survey. A total of 385 respondents within Festac town in Nigeria were selected stratifiedly for the study. Descriptive analysis showed that 64.9% of the respondents are passive while 35.1% are active complainers. Regression analyses revealed that six demographic variables explained 4.9% variance on complain behaviour while dissatisfaction explained additional 10% variance on complain behaviour. It further indicated that three control measures were significant, with dissatisfaction (β=-.33, p <.001), religion (β=.12, p <.05) and level of income (β=.11, p <.05). Dissatisfaction is an insubvertable factor of complain behaviour regardless of consumers’ religious affiliation and level of income. Firms should try to alleviate dissatisfaction, encourage active complain, and pay more attention to consumers’ religiosity and level of income since these variables influence complain behaviour.